Maternal hemoglobin associates with preterm delivery and small for gestational age in two Finnish birth cohorts. (July 2019) - Ronkainen, Justiina; Lowry, Estelle; Heiskala, Anni; Uusitalo, Iida; Koivunen, Peppi; Kajantie, Eero; Vääräsmäki, Marja; Järvelin, Marjo-Riitta; Sebert, Sylvain
Abstract: Objective: To test whether maternal hemoglobin during pregnancy associates with offspring perinatal outcomes in a developed country. Changes in maternal hemoglobin concentration during pregnancy are partly physiological phenomena reflecting alterations of maternal blood volume. Especially hemoglobin measures outside the physiological range may influence maternal health and fetal growth with long-lasting consequences. Study design: We studied an unselected sample drawn from two regional birth cohorts born 20 years apart: The Northern Finland Birth Cohorts 1966 and 1986. These are two mother-and-child population-based birth cohorts together comprising 21, 710 mothers and their children. After exclusions, the sample size of the current study was 20, 554. Concentrations of maternal hemoglobin at first and last antenatal visits were categorized as low (lowest 10%), medium (reference) or high (highest 10%). Multinomial logistic regression analyses for categories of maternal hemoglobin and perinatal outcomes such as preterm delivery and full-term small and large for gestational age were conducted with adjustments for maternal cofactors. Results: Low maternal hemoglobin at early pregnancy associated with decreased risk of full-term small for gestational age (adjusted OR 0.73, 95% CI [0.58, 0.93], p = 0.010). At late pregnancy, low maternal hemoglobin associated with increased risk of preterm delivery (adjusted OR 1.60, 95% CI [1.26, 2.02], p < 0.0005) whereas high maternal hemoglobin associated with increased risk of full-term small for gestational age (adjusted OR 1.29, 95% CI [1.07, 1.56], p = 0.009). Maternal hemoglobin did not show constant association with risk of large for gestational age. Conclusion: The results from this study support evidence that both low and high maternal hemoglobin associate with adverse perinatal outcomes. Low maternal hemoglobin associated with preterm delivery and high with full-term small for gestational age. Association was mainly present when maternal hemoglobin was measured during the third trimester. These results indicate that it is important to monitor both extremes of maternal hemoglobin throughout the pregnancy.